TRUE POWER LOSS REDUCTION BY HARMONY SEARCH ALGORITHM - Lenin, K. (International Journal of Research -GRANTHAALAYAH, 2018)
This paper presents Harmony Search algorithm (HS) for solving the reactive power problem. Real power loss minimization is the major objective & also voltage profiles are should be kept within the limits. This paper introduces a new search model the harmony search (HS) algorithm is a relatively new population-based metaheuristic optimization algorithm. It emulates the music improvisation progression where musicians improvise their instruments’ pitch by searching for a perfect state of harmony. In order to evaluate the efficiency of the proposed algorithm, it has been tested on practical 191 test system & real power loss has been considerably reduced.